Expression of the Grape VqSTS21 Gene in Arabidopsis Confers Resistance to Osmotic Stress and Biotrophic Pathogens but Not Botrytis cinerea - Huang, Li; Zhang, Songlin; Singer, Stacy D.; Yin, Xiangjing; Yang, Jinhua; Wang, Yuejin; Wang, Xiping (Frontiers in Plant Science, 2016)
Stilbene synthase (STS) is a key gene in the biosynthesis of various stilbenoids, including resveratrol and its derivative glucosides (such as piceid), that has been shown to contribute to disease resistance in plants. However, the mechanism behind such a role has yet to be elucidated. Furthermore, the function of STS genes in osmotic stress tolerance remains unclear. As such, we sought to elucidate the role of STS genes in the defense against biotic and abiotic stress in the model plant Arabidopsis thaliana. Expression profiling of 31 VqSTS genes from Vitis quinquangularis revealed that VqSTS21 was up-regulated in response to powdery mildew (PM) infection. To provide a deeper understanding of the function of this gene, we cloned the full-length coding sequence of VqSTS21 and overexpressed it in Arabidopsis thaliana via Agrobacterium-mediated transformation. The resulting VqSTS21 Arabidopsis lines produced trans-piceid rather than resveratrol as their main stilbenoid product and exhibited improved disease resistance to PM and Pseudomonas syringae pv. tomato DC3000, but displayed increased susceptibility to Botrytis cinerea. In addition, transgenic Arabidopsis lines were found to confer tolerance to salt and drought stress from seed germination through plant maturity. Intriguingly, qPCR assays of defense-related genes involved in salicylic acid, jasmonic acid, and abscisic acid-induced signaling pathways in these transgenic lines suggested that VqSTS21 plays a role in various phytohormone-related pathways, providing insight into the mechanism behind VqSTS21-mediated resistance to biotic and abiotic stress.